Healing at the periphery : ethnographies of Tibetan medicine in India (Duke University Press, 2021)
"The contributors to Healing at the Periphery examine Sowa Rigpa, or Tibetan medicine, and the central part practitioners of Tibetan healing known as amchis play in Indian Himalayan communities and the exile Tibetan community."--